A Novel Three-Step Tandem Reaction for Efficient Syntheses of Bulky Anthracenyl Esters from 2-Benzylbenzoic Acids - Wang, Yabai; Yang, Shiwei; Bian, Guangling; Song, Ling (Synthesis, 2017)
Bulky anthracenyl esters could be efficiently synthesized from 2-benzylbenzoic acids via a novel three-step tandem reaction containing intramolecular Friedel–Crafts acylation, enolization, and esterification. A mechanism for the tandem reaction is proposed.
Keywords: tandem reaction; Friedel–Crafts acylation; enolization; esterification; anthracenyl esters